Guarda compartilhada nos casos de violência doméstica do pai contra a mãe: melhor interesse da criança e do adolescente - Monteiro, Izabelle Pontes Ramalho Wanderley (2020)
This paper analyzes the shared custody of children and adolescents in family conflicts resulting from domestic violence practiced by the father against the mother, under the terms of the Law no. 11.340/2006. This approach was adopted because of the alarming numbers of domestic violence against women in intimate heterosexual relationships, as well as the understanding that, as recipients of the full protection doctrine and, therefore, with the right to grow up with health, dignity and saved from all forms of violence, children and adolescents are indirect victims of violence perpetrated between parents and experienced by them in family living. Using interdisciplinary studies, researches that confirmed the possibility of damage to the development of children and adolescents after experiencing the practices of violence by the father against the mother, were identified, as well as the cyclical and systematic nature of domestic violence that covers this problem of such complexity and difficulty in breaking it. In these terms, focusing on situations of marital break underlying this form of violence, especially those that result of the decree of emergency protective measures of incommunicability and distancing from the aggressor, under the terms of the Maria da Penha Law, this study is necessary to comprehend if the application of shared custody as a rule in Brazil, established by the Law No. 13,058 / 2014, reaches the best interest of children and adolescents in such cases. Using normative instruments, jurisprudential understandings and doctrinal debates, the research is exploratory, bibliographic and documentary, using the deductive approach method. In the perspective of the humanization of Civil Law, especially regarding to the special protection of hypervulnerable people, this study concluded that the application of shared custody as a rule in such cases does not guarantee the best interest of the child, also considering the need for a legislative improvement with a proposal for a possible initial removal, but with multidisciplinary monitoring that makes family living feasible and, progressively, allows the future reanalysis of sharing, depending on each case.